Successful treatment of a solitary skull metastasis in a child with Wilms' Tumor - Lucas A. McDuffie; Robert J. Fallon; Terry A. Vik; Deborah F. Billmire (Elsevier, 2017)
This report presents the successful treatment of a child with a solitary metastatic lesion to the calvarium following treatment for Stage III anaplastic Wilms' Tumor.